Co-transcribed genes SA1833-SA1832 promote persister formation by regulating the transcription of holin-like gene lrgA in methicillin-resistant Staphylococcus aureus strain N315 - Shiwen Xu; Jiade Zhu; Yujie Li; Baolin Sun (International Journal of Medical Microbiology)
Staphylococcus aureus, a facultative anaerobic gram-positive bacterial pathogen, has posed major threat to public health worldwide. Upon S. aureus infection, the host immune system is activated for clearance. However, intracellular S. aureus, which remains viable for an extended time, has evolved the ability to escape from immune response and extracellular antibiotics. One of possible strategies is the formation of persisters. Persistence is one of the major causes of S. aureus relapse infection but the underlying mechanisms remain obscure. Here, we identified two co-transcribed genes SA1833-SA1832 that are involved in persister formation in S. aureus. Dysfunction of SA1833 and/or SA1832 significantly reduces persister formation in the presence of ceftizoxime. Additionally, we found that the expression of SA1833 and SA1832 under the induction of oxidative stress and SOS response is strictly regulated by the LexA-RecA pathway. Interestingly, SA1833-SA1832 contributes to persister formation in an lrgA-dependent manner. Moreover, the mouse RAW264.7 macrophage infection model indicated that disrupting SA1833-SA1832 inhibits S. aureus from infecting macrophages and impairs its ability to survive in the intracellular environment.